(3+2)-Cycloaddition of Donor–Acceptor Cyclopropanes with Thiocyanate: A Facile and Efficient Synthesis of 2-Amino-4,5-dihydrothiophenes - Jacob, Anu; Barkawitz, Philip; Andreev, Ivan A.; Ratmanova, Nina K.; Trushkov, Igor V.; Werz, Daniel B. (Synlett, 2021)
An easy and efficient route to obtain 2-amino-4,5-dihydrothiophenes is presented. A formal (3+2)-cycloaddition of donor–acceptor cyclopropanes and ammonium thiocyanate catalyzed by Yb(OTf)3 delivers the desired products in good to excellent yields. A broad range of functional groups is tolerated during this process.
Keywords: D–A cyclopropanes; dihydrothiophenes; Lewis acid catalysis; thiocyanate; cycloaddition